2012
DOI: 10.1042/bsr20120031
|View full text |Cite
|
Sign up to set email alerts
|

Acute regulation of 5′-AMP-activated protein kinase by long-chain fatty acid, glucose and insulin in rat primary adipocytes

Abstract: Palmitate increased AMPK (5′-AMP-activated protein kinase) activity, glucose utilization and 2-DOG (2-deoxyglucose) transport in rat adipocytes. All three effects were blocked by the AMPK inhibitor Compound C, leading to the conclusion that in response to an increase in long-chain NEFA (non-esterified fatty acid) concentration AMPK mediated an enhancement of adipocyte glucose transport, thereby providing increased glycerol 3-phosphate for FA (fatty acid) esterification to TAG (triacylglycerol). Activation of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…Palmitate stimulated Akt phosphorylation in a time- and dose-dependent manner, and by inhibiting PI3K – which is upstream of Akt in the signal transduction pathway – glucose uptake was abolished by a blocking of Akt phosphorylation. Summarized, these results demonstrate the important role of this signaling pathway in the cell line examined, and similar results have been demonstrated in adipocytes [23]. It is tempting to suggest a similar effect of palmitate on the PI3K/Akt pathway in prostate cancer cells to explain the observations made in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Palmitate stimulated Akt phosphorylation in a time- and dose-dependent manner, and by inhibiting PI3K – which is upstream of Akt in the signal transduction pathway – glucose uptake was abolished by a blocking of Akt phosphorylation. Summarized, these results demonstrate the important role of this signaling pathway in the cell line examined, and similar results have been demonstrated in adipocytes [23]. It is tempting to suggest a similar effect of palmitate on the PI3K/Akt pathway in prostate cancer cells to explain the observations made in our study.…”
Section: Discussionsupporting
confidence: 92%
“…7). Similar to the effects of glucose and palmitate on AMPK activity in rat adipocytes (35), cardiomyocytes (36), and bovine aortic endothelial cells (91), we found that these nutrients decreased AMPK activity in HAECs. However, activation of AMPK was not sufficient to restore autophagy in this nutrientrich environment.…”
Section: Discussionsupporting
confidence: 55%
“…We and others have shown that high concentrations of glucose or palmitate impair AMPK activity (35,36,91) as well as SIRT1 activity (2,18,71,80). AMPK and SIRT1 have also been shown to regulate one another (11,39,55).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K inhibitor (wortmannin) hardly affected induction of CYP3A4 by PA. Several studies demonstrated that PA and OA induced both NFkB (57,58) and PKC activities (59,60), and the stimulatory effects of OA on the PKC pathway was stronger than those of PA (61,62). PA was also reported to inhibit phosphorylation of AMPK (63,64) and Akt (65,66). In sharp contrast, OA enhanced the activity of Akt (67) and showed weak inhibition on phosphorylation of AMPK (68).…”
Section: Discussionmentioning
confidence: 99%